Influence of rare-earth substitution on the structural, magnetic, optical and dielectric properties of ZnO nanoparticles. (5th February 2019) - Martínez, Ricardo; Zuluaga, Claudia; Dussan, Sandra; Huhtinen, Hannu; Jadwisienczak, Wojciech; Palai, Ratnakar
Abstract: We report on structural, magnetic, optical, and dielectric properties of rare earth (Er and Yb)-doped ZnO nanoparticles with Na-co-doping for charge compensation by sol-gel process. The effect of doping concentration on the structural and dielectric properties of ZnO has been studied under magnetic field and UV excitation. The magnetodielectric and photodielectric effects at room temperature of doped ZnO are discussed in the light of magnetic and optical properties of Er 3+ and Yb 3+ ions.